Initial treatment with a single capsule containing half-dose quadruple therapy vs standard-dose dual therapy in hypertensive patients (QUADUAL): a randomized, blinded, crossover trial - Xiexiong Zhao; Tao Liu; Qiong Yang; Guoping Yang; Xingli Li; Xiaohong Tang; Jingle Li; Zhongshu Liang; Anying Li; Lixiong Zeng; Juan Wen; Xiaoyan Wang; et al. (BMC Medicine)
Abstract Background Guidelines recognized dual combination in initial antihypertensive therapy. Studies found that low-dose quadruple combination were superior to monotherapy. However, whether low-dose quadruple therapy is better than dual combination is unknown. Methods A randomized blinded crossover trial was conducted to compare the efficacy and safety of low-dose quadruple antihypertensives (irbesartan 75 mg + metoprolol 23.75 mg + amlodipine 2.5 mg + indapamide 1.25 mg) with standard-dose dual antihypertensives (irbesartan 150 mg + amlodipine 5 mg), both in a single pill, in the initial treatment of patients with mild to moderate hypertension. Patients were randomly assigned in a 1:1 ratio to two crossover sequences. Each sequence received four-weeks of either half-dose quadruple antihypertensives or standard-dose dual antihypertensives, followed by a two-week washout and crossover for four-weeks. Participants and researchers were blinded. The main outcomes were the reduction of blood pressure and safety outcomes. Analyses were per intention to treat. Results A total of 90 eligible participants were randomized between July 13, 2022, and April 20, 2023. The mean age was 43.88 years (SD 10.31), and 25.6% were women. The mean baseline 24-h blood pressure was 145.59/93.84 mm Hg. Compared to the standard-dose dual treatment, the half-dose quadruple treatment resulted in a further reduction in mean 24-h blood pressure by 4.72/4.17 mm Hg (P < 0.001 for both systolic and diastolic blood pressure), mean daytime blood pressure by 5.52/4.73 mm Hg (P < 0.001 for both), mean nighttime blood pressure by 2.37/2.25 mm Hg (P = 0.034 and 0.014, respectively), and mean office blood pressure by 2.91/1.73 mm Hg (P < 0.001 and 0.014, respectively). Apart from significant increases of fasting blood glucose (P = 0.029) and blood uric acid (P < 0.001) in the half-dose quadruple group, no other adverse events or changes in laboratory values differed significantly between the two treatments. Conclusions Initiating treatment with half-dose quadruple combination therapy was more effective in lowering blood pressure than standard-dose dual therapy. The safety of half-dose quadruple therapy was comparable. Trial registration ClinicalTrials.gov Identifier: NCT05377203.